Neither Isle Nor Peninsula (2006)
This article picks up Zoe Valdes’s idea of a primacy of the cultural influences of old Cuban aboriginals and forced African immigrations. The text focuses on the historical and cultural elaboration of indigenous and African ethnic groups, at the expense o